Effective Humanitarian Work: Teaching Medical Skill Sets in Ukraine - Michael S. Baker; Rom A. Stevens; Jacob Baker (Ubiquity Press, 2023)
The senior authors traveled to Ukraine to teach specific skills to Ukrainian physicians and other medical professionals, utilizing a 2-day ATLS course, workshops in point-of-care ultrasonography (POCUS), lectures and webinars on damage control resuscitation, damage control surgery, and transfusion of whole blood. The authors have focused on providing skill sets that Ukrainian doctors can utilize within their existing system to improve immediate patient care for casualties resulting from the unanticipated Russian invasion and improve outcomes. Given the resource limitations and differences of the Ukrainian healthcare systems, the authors believe Western-based professionals who come to Ukraine to help for short periods should resist the temptation to offer western solutions that may not work in Ukraine. Major improvements in Ukrainian health care will require long-term efforts in teaching but also need to include increased efforts to improve hospitals, clinics, staffing, education, supplies, and equipment. Those who travel to help in Ukraine can still teach short courses that provide skills that Ukrainian doctors and nurses can use within their existing healthcare system to improve the quality of patient care in the immediate period of crisis and hopefully improve outcomes in the near term. It is not a reasonable expectation to think that the delivery of 2-day courses such as ATLS or POCUS will significantly change the country-wide delivery of healthcare. This sort of practice change requires the engagement of medical and political leaders and a sustained reform effort over years, not days or weeks. Supportive countries and non-governmental organizations need to prepare for a long and extensive investment in improving Ukrainian healthcare.